Perancangan Aplikasi Layanan Foto Prewedding Berbasis Mobile Menggunakan Model Waterfall - Aqilla Fadia Hafizhah; Karnadi Karnadi; Muhammad Ihsan (Bulletin of Computer Science Research, 2025)
This research aims to design a mobile-based pre-wedding photo service application that can simplify the ordering process, speed up communication between customers and photo studios, and improve operational efficiency. The research method used is a qualitative method with data collection techniques through observation and literature studies. The system development method used by the waterfall model. The application is implemented using Android Studio with the kotlin and java programming languages and the firebase database. The result of this implementation is in the form of a mobile-based prewedding photo service application that has registration, login, photo selection, ordering, order confirmation, transaction history, package management and photo collection by admins, as well as revenue reports that can be accessed by the owner. Based on the results of tests using the blackbox method, all application features can run well and according to user needs. With this application, it is hoped that Studio Photo Holic can improve the quality of service and provide convenience for customers in ordering prewedding photo services.